Microsurgery training: A combined educational program. (December 2020) - Beris, Alexandros; Kostas-Agnantis, Ioannis; Gkiatas, Ioannis; Gatsios, Dimitrios; Fotiadis, Dimitrios; Korompilias, Anastasios
Highlights: Microsurgery education should be intensive. Microsurgery education should be performed in both living and non-living models. Evaluation of the trainee should be added in the training programs. New technologies should be inserted in the training. Abstract: A proposed microsurgical training program is presented that includes all the existing training methods, such as simulation in nonliving models, virtual reality simulation system and exercise in living models. Our experience in microsurgery training over the last decades indicates the need of evolution in training programs. This can be achieved with the introduction of new technologies into education and training. The first primary results of the described training program are promising, however this system needs to be assessed by training greater number of microsurgeons. Furthermore, more complex scenarios (such as whole operations) should be inserted into the virtual reality simulation system to create a more interactive experience.